The Critical Role of a Positive Self-Esteem - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
The appeal and attractiveness of people differ tremendously as reflected on their confidence, performing abilities, and gain of respect. While successful individuals are usually self-reliant and present high verbal and socializing competence, many others are shy, suppress their thoughts and feelings in an attempt to hide their weaknesses, and so their appeal and gain of respect are evidently limited. One major reason behind such behavioral disparity is the vast differences in state of mind and self-esteem. Since the self-esteem of people is largely based on an inner evaluating perception and is also exposed to environmental critique, its durability requires continuous strengthening and success, as well as mental stability and decisive personality. A constructive self-esteem usually develops during childhood and depends on success and positive feedback of the parents, teachers, and the environment. In general, success at school, in sport, in social interactions, or due to a particular talent may strengthen the confidence and contribute to the buildup of a positive self-esteem. Further progressive development may persist during adulthood, requiring periodical reinforcements (e.g., upon the establishment of a new family or a professional success) with developed positive manners, increased confidence, and a respectable appearance. However, even a good start during childhood may decline in the lack of further success or upon development of annoying habits. If a child is not very clever, good looking or talented, his/her appreciation by the teachers, parents and friends is reduced, which may affect his/her self-esteem. Then, the development of confidence and improvement of the self-esteem and eloquence may be quite laborious. For these reasons, parents with high desires for their children, are willing to invest much for an early good start and gain of high self-esteem. Growth in deprived environment with uneducated parents and poor resources may limit the development of a high self-esteem, and trigger disappointment and even paranoia, which may lead to aggression and belligerence. While individuals with low self-esteem won’t invest too many efforts due to limited expectations, over fostering may lead to exaggerated self-esteem, audacity (‘Chutzpah’), and extremism, all projecting emotionally and in vicious behavior, thus reducing their attractivity. A negative self-esteem builds up on the basis of many factors, some of which may rest on prejudice ideas and immense self-critique. Since prejudice ideas usually get fixed in the mind of particularly younger people and are very hard to change (Martin Buber: prejudices of youth), open discussions, non-stagnated minds, positive approach, and verbal abilities are important already at early developmental stages.